The relation between IT competency and knowledge management processes and its mediators - Susana Pérez-López; Beatriz Junquera (Tourism & Management Studies)
The past two decades have seen growing interest in knowledge management and the use of information technologies. However, it is not clear how the relation between IT competency and knowledge management works. This study provides a better understanding of that relation. Through an empirical study of 162 Spanish firms, the work finds that no direct relation exists between IT competency and knowledge management. Open organization and empowerment mediate the relation between IT competency and knowledge management processes. These findings reinforce a field that is of increasing interest to researchers, and which has seen only a limited number of empirical studies to date.